PENGARUH PROSES MASERASI DENGAN VARIASI KONSENTRASI PELARUT ETANOL TERHADAP KANDUNGAN SENYAWA EKSTRAK DAUN PEPAYA (Carica papaya L.) DAN DAUN UBI JALAR UNGU (Ipomoea batatas L. Lam) - Herman Irawan; Sevty Syera; Nurlaili Ekawati; Djadjat Tisnadjaja (Jurnal Ilmiah Manuntung, 2020)
Papaya (Carica papaya L.) and purple sweet potato (Ipomoea batatas L. Lam) are commonly used empirically as traditional medicines, including for malaria, malnutrition, fever and hemorrhagic fever. The purpose of this study was to determine the effect of differences in the concentration of ethanol solvents on the chromatogram profile and compound content. The research method began with maceration using 50%, 70%, and 96% ethanol, then thin layer chromatography test, and determination of total phenol and flavonoid levels with Elisa at λ of 750 nm and 415 nm, where the comparator used were gallic acid and quercetin . The results of total phenol levels obtained in papaya leaf extract were 3,493 mg GAE/gram and in sweet potato leaves the results were 4,786 mgGAE/mg. While the total flavonoid yield obtained from papaya leaf extract was obtained as much as 4,630 mg QE/gram and on sweetpotato which was 4,269 mgQE/mg. Characterisation of extract compound content was carried ouy by using Gas Chromatography- Mass Spectroscopy (GC-MS), where comparison of extracts used in extract combination samples are 50:50, 75:25, and 25:75. The results showed that ethanol extract contained alkaloids, flavonoids, saponins, tannins, and triterpenoids. Characterization by using GC-MS for single extract and combination extract of papaya leaves and purple sweet potato leaves obtained the main active compounds are Phytol, Neoheptadine, and n-Hexadecanoic acid.